Studies of agronomic performance of quinoa (Chenopodium quinoa Willd.)genotypes under arid conditionsof northeast of the Algerian Sahara(Case of Ouedrigh) - Oustani, Mabrouka; Halilat, Mohammed Tahar; Mahda, Smail (University of Eloued جامعة الوادي, 2019)
The varietal behavior of six quinoa genotypes (Giza1, Sajama, Santa Maria, Q102, Q29, Q27 and Q18) was monitored under arid conditions of Ouedrigh region. The adopted experimental device is ofrandom block type (with four blocks).Measurements includedemergence rate, seed yield and thousand kernel weight. The obtained results showed that all the genotypes tested detected an adaptive potential to the extreme edapho-climatic conditions of the arid environment with a high germinating ratefor all genotypes. The best yield was in favor of genotype Q102 (302.21g m-2). While, thelowest yield was recorded by the Santa Maria genotype which recorded a yield of the order of (203.33g m-2). The obtained results show that quinoa holds great promise as a newcropintheagriculturalproductionsystemsinsouthofAlgeriaadaptsverywellwiththepedoclimatic conditions of Algeria.
الملتقى الدولي السابع حول اقتصاديات الإنتاج الزراعي في ظل خصوصيات المناطق الزراعية في الجزائر والدول العربية 30- 31 أكتوبر 2019 كلية العلوم الاقتصادية والتجارية وعلوم التسيير جامعة الشهيد حمه لخضر الوادي
Keywords: Quinoa, Varietal Behavior, Adaptation, Arid Conditions